La « culture » dans les grammaires amérindiennes - Cédric Becquey; Valentina Vapnarsky; Cédric Yvinec (Nuevo mundo - Mundos Nuevos, 2014)
Amerindian languages have often borrowed the lexical terms of colonial languages that refer to “culture”, “tradition” or “heritage”, or they have created neologisms from these terms. However, in Amerindian languages, these notions were already expressed by various syntactic forms and constructions, rather than by lexical terms, such as aspectual and temporal configurations, epistemological and evidential modality, expressions of person and agency. These syntactic forms reveal how these languages and cultures construct notions like “culture” or “tradition”, and bring up questions about the various kinds of reflexivity and typification that syntactic or lexical encodings imply. The linguistic material used in this article is based on various languages that were studied in the project: Chol, Kakataibo, Yucatec Maya, Suruí, Tseltal, Yurakaré…).